Extraction of bioactive compounds from juçara palm residue and application in biodegradable packaging - Januário, Jaqueline Gilmara Barboza; Silva, Jaqueline Ferreira; Santos, Suelen Siqueira dos; Scapim, Mônica Regina da Silva; Madrona, Grasiele Scaramal (Revista em Agronegócio e Meio Ambiente, 2024)
The processing of the fruit of the Juçara palm tree Euterpes edulis Martius generates solid residue that is discarded by the industry, although it still has a composition rich in bioactive compounds. This study aimed to extract bioactive compounds from the skin of the juçara palm fruit and apply them in the form of microcapsules in biodegradable packaging. The extract was obtained using thermal bath and ultrasound extraction techniques, followed by microencapsulation and freeze-drying. The capsules produced were added to films using the casting technique. The extracts were evaluated for total phenolic compounds, antioxidants (DPPH, ABTS, FRAP), flavonoids and anthocyanins. The films were evaluated for thickness, water vapor barrier properties and mechanical properties. The results were submitted to analysis of variance (ANOVA) and Tukey's test (p<0.05). The encapsulation and freeze-drying process of the extracts allowed an improvement in the antioxidant values of the extracts. The films presented a smooth surface and good malleability. In general, the films added to the capsules presented greater flexibility due to the greater value of elongation at break, lower stiffness due to the lower value of Young's Modulus, had greater permeability to water vapor (PVA) and did not present statistical differences in